'So maybe I'm a global citizen': developing intercultural citizenship in English medium education. Issue 1 (2nd January 2021) - Baker, Will; Fang, Fan (Gabriel)
ABSTRACT: A frequently stated aim of the increasing internationalisation of higher education (HE) is the incorporation of intercultural elements. This has recently been conceptualised through the notion of intercultural citizenship with universities promising to equip graduates with the necessary knowledge and skills to engage in global workplaces and communities. However, the extent to which intercultural citizenship goes beyond promotion and marketing and is meaningfully incorporated into university curricula and teaching practices is still unclear. Most significantly, there is little evidence that students themselves are aware of, motivated by, or develop a sense of intercultural citizenship at international universities. In parallel to the expansion of internationalisation in HE has been an increase in English medium instruction (EMI) programmes. This link between the use of English and internationalisation is therefore likely to also influence perceptions of intercultural citizenship but has so far received little attention in research. To address these gaps this study investigated the perceptions and experiences of international students towards intercultural citizenship and its links to language before, during and after their study via interviews and a focus group. Findings showed intercultural citizenship was generally positively perceived and strongly linked to English, but reported development was uneven during study abroad.